Papua New Guinea Riots in January 2024: Exploring the Impact and Securitization Process Behind Instability - Gustiawarman, Defri; D'Novaliano, Ryvo; Setiawan, Roy (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2025)
Papua New Guinea is a developing country located in Oceania within the specifications of the Melanesian family. Papua New Guinea in the status quo condition still faces various forms of domestic problems that have an impact on internal instability conditions. Acts of unrest are still massive in this country, which has an impact on poor economic conditions and a high poverty rate targeting all levels of the population. In January 2024, the international community was shocked by the news of riots that occurred in several cities in Papua New Guinea namely Port Moresby and Lae, due to the phenomenon of unilateral salary cuts to state civil servants without any further explanation from the government. The rioting by civil servants (police, public sector staff, and other civil servants) and opportunistic parties has had a huge impact on the internal conditions of the country forcing the city into a precarious situation and this phenomenon itself is exacerbated by the vacant position of the security forces due to their participation in this action. The unrest had a huge impact and led to acts of violence, murder, and looting aimed at several shops in the corners of the city. In response, James Marape as the Prime Minister of Papua New Guinea declared a national emergency for two weeks and attempted to bring in securitization measures to reduce the larger conflict that could break out at any time. Keywords: Papua New Guinea, Riot, Instability, Securitization